2023
DOI: 10.17762/ijritcc.v11i5s.6636
|View full text |Cite
|
Sign up to set email alerts
|

Aspect-Based Sentiment Analysis using Machine Learning and Deep Learning Approaches

Abstract: Sentiment analysis (SA) is also known as opinion mining, it is the process of gathering and analyzing people's opinions about a particular service, good, or company on websites like Twitter, Facebook, Instagram, LinkedIn, and blogs, among other places. This article covers a thorough analysis of SA and its levels. This manuscript's main focus is on aspect-based SA, which helps manufacturing organizations make better decisions by examining consumers' viewpoints and opinions of their products. The many approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…The significant works done for aspect term extraction and aspect-based sentiment analysis in general and in the Hindi language are discussed in the literature survey (3)(4)(5)(6)(7)(8) . Md Shad Akhtar et al (9) reported the first supervised approach to the aspect term extraction task; they created an annotated dataset of high quality and built a machine learning model for sentiment analysis to show practical usage of the dataset.…”
Section: Related Workmentioning
confidence: 99%
“…The significant works done for aspect term extraction and aspect-based sentiment analysis in general and in the Hindi language are discussed in the literature survey (3)(4)(5)(6)(7)(8) . Md Shad Akhtar et al (9) reported the first supervised approach to the aspect term extraction task; they created an annotated dataset of high quality and built a machine learning model for sentiment analysis to show practical usage of the dataset.…”
Section: Related Workmentioning
confidence: 99%